Epithelioid Angiosarcoma Arising in an Adrenal Cortical Adenoma: A Case Report and Review of the Literature. (December 2014) - Hendry, Shona; Forrest, Cynthia
Adrenal masses are common incidental imaging findings, with the majority comprising benign adrenal cortical adenomas. However, the differential diagnosis is extensive and includes both primary and secondary malignant lesions. Primary adrenal angiosarcomas are rare and often exhibit epithelioid morphology, which can present a diagnostic pitfall. We report an exceptional "incidentaloma" in a 60-year-old lady, which showed the features of a primary epithelioid angiosarcoma arising within an adrenal cortical adenoma. No other primary tumor was identified on extensive imaging. This unusual combined tumor has been reported only once before, to the best of our knowledge. The pattern of infiltration of the malignant endothelial cells raises the suggestion that the angiosarcoma arose from vascular elements of the adenoma.